Les insectes et le Sillon Dahomeen: fragmentation et refuges forestiers - Le Gall, P.; Goergen, Georg E.; Neuenschwander, Peter (2002)
South Eastern Ghana and the south of Togo and Benin constitute a biogeographically remarkable area, called the Dahomey Gap, whose entomological fauna is stilliittie known despite its unique features. The geographical barrier separating this region from the two forest blocks with wetter climates, in the east and the west, is more strongly marked in Ghana th an in Benin, where relict forests still exist. They sustain an in sect fauna belonging to either the western or eastern forest block, with few species being represented in both blocks. The presence of endemic species contributes significantly to the definition of this controversial region. A dozen insect species are provisionally defined as being endemic to the Dahomey Gap.